Genetic risk variants for social anxiety - Stein, Murray B.; Chen, Chia‐Yen; Jain, Sonia; Jensen, Kevin P.; He, Feng; Heeringa, Steven G.; Kessler, Ronald C.; Maihofer, Adam; Nock, Matthew K.; Ripke, Stephan; Sun, Xiaoying; Thomas, Michael L.; et al. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2017)
Social anxiety is a neurobehavioral trait characterized by fear and reticence in social situations. Twin studies have shown that social anxiety has a heritable basis, shared with neuroticism and extraversion, but genetic studies have yet to demonstrate robust risk variants. We conducted genomewide association analysis (GWAS) of subjects within the Army Study To Assess Risk and Resilience in Servicemembers (Army STARRS) to (i) determine SNP‐based heritability of social anxiety; (ii) discern genetic risk loci for social anxiety; and (iii) determine shared genetic risk with neuroticism and extraversion. GWAS were conducted within ancestral groups (EUR, AFR, LAT) using linear regression models for each of the three component studies in Army STARRS, and then meta‐analyzed across studies. SNP‐based heritability for social anxiety was significant (h2g = 0.12, P = 2.17 × 10−4 in EUR). One meta‐analytically genomewide significant locus was seen in each of EUR (rs708012, Chr 6: BP 36965970, P = 1.55 × 10−8; beta = 0.073) and AFR (rs78924501, Chr 1: BP 88406905, P = 3.58 × 10−8; beta = 0.265) samples. Social anxiety in Army STARRS was significantly genetically correlated (negatively) with extraversion (rg = −0.52, se = 0.22, P = 0.02) but not with neuroticism (rg = 0.05, se = 0.22, P = 0.81) or with an anxiety disorder factor score (rg = 0.02, se = 0.32, P = 0.94) from external GWAS meta‐analyses. This first GWAS of social anxiety confirms a genetic basis for social anxiety, shared with extraversion but possibly less so with neuroticism. © 2017 Wiley Periodicals, Inc.